Non-governmental organization in the Republic of Kazakhstan: their role in energy policy formation - К. Dzhangabulova A.; Kline, 2Thomas R.; A, Erezhepkyzy R.; L., Baideldynov D.; G., Alimzhanova M. (Farabi Journal of Social Sciences, 2019)
Abstract. The status and direction of development of the NGO sector in the Republic of Kazakhstan and its role in the development of a democratic society are discussed in the article. The last decade of the 20th century clearly shows that NGOs have been considered by donors as a core of civil society, which implements social projects and invests the development of democracy are key figures of democratization of the society. The relevance and importance of the non-governmental organizations roles in both policy of individual states and internationally are noted. The interaction of the non-governmental sector and the state, the effect of this interaction on the development of society are considered. The paper notes the lack of interaction of the state bodies and non-governmental organizations in the implementation of the energy security. Possible ways of activities and mechanism of participation of the non-governmental organizations in control of production and transportation of energy, including, the recommendations development to increase the manufacturers’ responsibility for environmental pollution, the establishment a mechanism for independent monitoring compliance of environmental legislation are offered.